What will you be, Grandma? (Brubaker, Ford & Friends, 2011)
Every child is asked again and again what they want to be when they grow up, but will Grandma have the answer when granddaughter Lily turns the tables and asks her the question? This delightful story is a perfect book to share with a grandmother and strikes a perfect balance between touching and humorous